Fabrication and Multi scale Characterization of Functionally Graded Composites Reinforced with Hybrid Ceramic–Metallic Phases - Dr PNS Srinivas; Dr. Ch.V.S.Parameshwara Rao; Rajkumar Goswami (International Journal of Mechanical Dynamics and Systems Analysis, 2025)
Using composite materials as functionally graded composites (FGM) can improve its excellent material properties. In this work, magnesium peroxide, silicon carbide, and aluminum are used to create four-layer FGMs. The sintering process, which blends the particles of each material using a powder methodology, has been used to complete the fabrication process. Three factors, including sintering time, sintering temperature, and compacting pressure, are taken into account when fabricating FGM. The FGM is composed of four layers: 90%Al+10%SiC, 90%Al+5%SiC+5%MgO2, 85%Al+5%SiC+10%MgO2, and 100% pure aluminum. To determine the mechanical, tribological, and micro structural properties, the produced FGMs were examined. Using scanning electron microscopy, the microstructure and worn-out surface of the FGM layers are examined. The main vital function of the functionally graded materials is to enhance step wise or slow gradation of the material properties such as mechanical, micro structural and tribological properties such that the all the properties are enhanced in increasing order. The synthesized materials are used in various special applications like aeronautical and space research, automobiles like racing bikes and cars and satellite applications. The mechanical analysis looks into the FGM material's compressive strength and hardness properties. The results of the mechanical analysis show that the FGMs outperform the composite materials in terms of compressive strength, micro hardness, and macro hardness, with values of 315 MPa, 1.26 GPa, and 1.87 GPa, respectively. The best process parameters in terms of mechanical properties have finally been found using Taguchi optimization. Taguchi optimization is not only based on optimization of the functional parts but also selection of correct and influential parameters such as compaction time, pressure, sintering time and temperature and required hardness which is increased enormously in the composition such as 5% SiC. According to the Taguchi optimization results, the mechanical properties of FGM are largely determined by the sintering temperature and only marginally by the sintering time and compacting pressure.
Keywords: Composites; Functionally graded materials; hybrid reinforcements; mechanical characterization; thermal behaviour